Desafios da (in)formação docente: o trabalho pedagógico com as artes na escolarização - Ricardo Ottoni Japiassu Vaz (EccoS – Revista Científica)
The article discusses the room of art teaching in Brazilian teachingprograms and signs Schöns reflective practitioner model as an alternative way tocorrect some distorted features of these programs. Some results from participantobservations developed by the author are depicted in help of his theoricarguments. It also considers diferent approaches to literacy by macro and microeducational policies in Brazilian schooling.